Is it just religious practice? Exploring patients' reasons for choosing a faith-based primary health clinic over their local public sector primary health clinic - James D. Porter; Graham Bresick (AOSIS, 2017)
Background: Person-centred, re-engineered primary health care (PHC) is a national and global priority. Faith-based health care is a significant provider of PHC in sub-Saharan Africa, but there is limited published data on the reasons for patient choice of faith-based health care, particularly in South Africa. Aim: The primary objective was to determine and explore the reasons for patient choice of a faith-based primary care clinic over their local public sector primary care clinic, and secondarily to determine to what extent these reasons were influenced by demography. Setting: The study was conducted at Jubilee Health Centre (JHC), a faith-based primary care clinic attached to Jubilee Community Church in Cape Town, South Africa. Methods: Focus groups, using the nominal group technique, were conducted with JHC patients and used to generate ranked reasons for attending the clinic. These were collated into the top 15 reasons and incorporated into a quantitative questionnaire which was administered to adult patients attending JHC. Results: A total of 164 patients were surveyed (a response rate of 92.4%) of which 68.3% were female and 57.9% from the Democratic Republic of the Congo (DRC). Of patients surveyed, 98.2% chose to attend JHC because 'the staff treat me with respect', 96.3% because 'the staff are friendly' and 96.3% because 'the staff take time to listen to me'. The reason 'it is a Christian clinic' was chosen by 70.1% of patients. 'The staff speak my home language' was given as a reason by 61.1% of DRC patients and 37.1% of South African patients. 'The clinic is close to me' was chosen by 66.6% of Muslims and 40.8% of Christians. Conclusion: Patients chose to attend JHC (a faith-based primary care clinic) because of the quality of care received. They emphasised the staff-patient relationship and patient-centredness rather than the clinic's religious practices (prayer with patients). These findings may be important in informing efforts to improve public sector primary care.